2008
DOI: 10.1093/eurheartj/ehn525
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic threshold levels of NT-proBNP testing in primary care

Abstract: We identified prognostic threshold levels for mortality and CV hospitalization for NT-proBNP in primary care patients suspected of HF. Our results have the potential to be used to risk-stratify waiting lists for echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Rosenberg et al in a large group of 5875 cardiac patients showed significant relation of elevated NT-proBNP in a range 83 -118 pg/ml with a 90% increased risk for cardiovascular mortality within three years of follow-up. Elevations above 83 pg/ml were found in 7,7% of our survivors, none of our volunteers had elevated values of this marker [26].…”
Section: Discussionmentioning
confidence: 42%
“…Rosenberg et al in a large group of 5875 cardiac patients showed significant relation of elevated NT-proBNP in a range 83 -118 pg/ml with a 90% increased risk for cardiovascular mortality within three years of follow-up. Elevations above 83 pg/ml were found in 7,7% of our survivors, none of our volunteers had elevated values of this marker [26].…”
Section: Discussionmentioning
confidence: 42%
“…[24][25][26][27][28][29][30] In spite of the fact that these tools are widely available and frequently introduced in clinical settings, the cardiac structural and functional remodeling studied by utilizing TDI and RT3D has rarely been conducted in patients with OSAS to evaluate their cardiac function. [31][32][33][34][35][36][37] In addition, the frequent coexistence of OSAS and congestive heart failure in clinical scenarios make it difficult to clearly define the exact impact of OSAS on cardiac remodeling and function, and vice versa.…”
Section: Brief Summarymentioning
confidence: 99%
“…25) High levels of NT-proBNP in the blood are characterized by a large molecular weight, and NTproBNP has a long half-life compared to BNP. 25) Measurement of NTproBNP is possible in serum, as it has a more stable value than BNP. We found that the median value of NTproBNP was higher at PPD7 than at GW36 or PPM1.…”
Section: Discussionmentioning
confidence: 99%